SMU's Logo (Institutional Knowledge at Singapore Management University, 1999)
Provost Tan Chin Tiong speaking at a press conference introducing Singapore Management University's new logo. The gold and dark blue logo of a lion's face is constructed from the seven geometric pieces of a traditional tangram puzzle. The press conference was held at library@Orchard on 15 December 1999.